Genetic manipulation of sex ratio in mammals: the Reaper comes for Mickey. (1st July 2019) - Smanski, Michael J; Zarkower, David
Abstract : In most animals, sexual reproduction results in a 1:1 ratio of females to males. For several sectors of agriculture, for example, milk or egg production, only a single sex is needed. Biasing the sex ratio so that only offspring of the desired sex are produced has the potential to increase breeding efficiency. In this issue of EMBO Reports, Yosef et al [1] demonstrate a genetic approach to bias the sex ratio in mice by specifically disrupting essential genes in male embryos. Their approach is an important first step toward generating sex‐ratio biasing applications for agriculture. Abstract : Biasing the sex ratio has the potential to increase breeding efficiency in agriculture. A study in this issue describes a genetic approach to bias the sex ratio by specifically disrupting essential genes in male mouse embryos.